THE HUBUNGAN ANTARA INDEKS MASSA TUBUH (IMT) KATEGORI OVERWEIGHT DAN OBESITAS DENGAN KELUHAN LOW BACK PAIN (LBP) PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Negara, Kade Ngurah Dwi Putra; Wibawa, Ari; Purnawati, Susy (Majalah Ilmiah Fisioterapi Indonesia, 2015)
This study was conducted to determine the relationship between body mass index in the overweight and obese categories with complaints of low back pain in students at the Faculty of Medicine, University of Udayana. This study used a cross sectional study design, where the population of this study was students in Udayana University Faculty of Medicine. Sampling technique in this study is simple random sampling, in which the samples have fulfilled the inclusion and exclusion criteria. The total number of sample was 61 people, in accordance with the calculation of sample size. LBP complaints were measured using questionnaires and LBP inspection conducted by physiotherapist. To determine the relationship between body mass index in the overweight and obese categories with complaints of low back pain, a chi-square test was performed. The result showed that there was significant association between body mass index in categories of overweight and obesity with complaints of low back pain at Udayana University Faculty of Medicine, with a p-value of 0.01 (p <0.05).
Keywords: Body Mass Index, overweight, obesity, Low Back Pain